2013
DOI: 10.1007/s12011-013-9836-z
|View full text |Cite
|
Sign up to set email alerts
|

Wi-Fi (2.45 GHz)- and Mobile Phone (900 and 1800 MHz)-Induced Risks on Oxidative Stress and Elements in Kidney and Testis of Rats During Pregnancy and the Development of Offspring

Abstract: The present study was designed to determine the effects of both Wi-Fi (2.45 GHz)- and mobile phone (900 and 1800 MHz)-induced electromagnetic radiation (EMR) on oxidative stress and trace element levels in the kidney and testis of growing rats from pregnancy to 6 weeks of age. Thirty-two rats and their 96 newborn offspring were equally divided into four different groups, namely, control, 2.45 GHz, 900 MHz, and 1800 MHz groups. The 2.45 GHz, 900 MHz, and 1,800 MHz groups were exposed to EMR for 60 min/day durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…In previous studies, Özorak et al () applied 2.45 GHz EMR for 1 h day −1 during the pregnancy and growth, and showed that EMR increased lipid peroxidation (LPO) and decreased TAS levels in the testes tissue, and Oksay et al () showed an increase in LPO in exposed rats. All of these findings were similar to the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, Özorak et al () applied 2.45 GHz EMR for 1 h day −1 during the pregnancy and growth, and showed that EMR increased lipid peroxidation (LPO) and decreased TAS levels in the testes tissue, and Oksay et al () showed an increase in LPO in exposed rats. All of these findings were similar to the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Milankot et al stated that GSH levels decreased and lipid peroxidation increased in testis of rats that were exposed to 0.9/1.8 GHz radiation for 1 hour a day for a period of 28 days (21). In another study, neonatal rats were exposed to 2.45 GHz (Wi-Fi), 900 MHz and 1800 MHz (mobile phone) for 60 minutes a day for a period of 6 weeks and at the end of the 4th, 5th and 6th weeks, kidney and testis tissue samples showed a decrease in GSH, glutathione peroxidase and total antioxidant capacity, and an increase in lipid peroxidation (22). Similar results of these studies support our fi ndings.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation and oxidizable iron content increased and antioxidant trace elements (copper and zinc), and glutathione levels decreased during kidney and testis development 18 .…”
Section: Female Sexual Function and Fertility Disordersmentioning
confidence: 99%